“Staggering” Effect in Even-even Nuclei with Quadrupole and Octupole Deformations - Nadirbekov, M.S.; Yuldasheva, G.A. (Ukrainian Journal of Physics, 2022)
The ∆I = 1 "staggering" effect is investigated in the energy spectrum of positive and negative parities of the yrast band of even-even actinide nuclei. The "staggering" effect is described by the formula proportional to the discrete approximation of the fourth-order derivative of the function ∆E(I). It is shown that the "staggering" effect is characterized by the "zigzag" behavior and does not vanish within the observed range of angular momenta.